Comparison of safety and efficacy in venous access closure using a double purse string suture technique vs. Z-suture technique after MitraClip procedure - Anas Alnaimi; Sebastian Frederik Mause; Nawar Alachkar; Jörg W. Schröder; Mathias Burgmaier; Mathias Burgmaier; Ertunc Altiok; Nikolaus Marx; Sebastian Reith; Sebastian Reith; Mohammad Almalla; Mohammad Almalla (Frontiers in Cardiovascular Medicine)
BackgroundPercutaneous mitral valve repair using the MitraClip System is a well-established therapeutic option for patients with symptomatic mitral regurgitation. This procedure is usually performed via venous femoral access using a 24-French guiding catheter. Since vascular complications and bleeding remain a relevant limitation, we now compared access closure using subcutaneous absorbable double purse string suture (DPSS) and Z-suture technique following MitraClip procedure.Methods249 patients (mean age 76 ± 8 years) who underwent MitraClip procedure at our institution were included. Venous closure was performed using Z-suture technique in 140 patients and DPSS technique in 109 patients. Vascular complications and bleeding events were assessed according to the Mitral Valve Academic Research Consortium (MVARC) criteria.ResultsMVARC minor and major vascular complications were comparable after closure with Z-suture and DPSS-technique (4.3% vs. 0.9%, p = 0.11 and 1.4% vs. 0.9%, p = 0.71, respectively). However, development of AV-fistula and requirement of access related surgical intervention was more often observed in the Z-suture group (5% vs. 0%, p = 0.018 and 3.5% vs. 0%, p = 0.045). MVARC minor and major, non-life-threatening bleeding did not differ between the two groups (10.7% vs. 12.9%, p = 0.61 and 0.7% vs. 0.0%, p = 0.38). Similarly, overall transfusion rates and access related blood transfusion rates were comparable (11.4% vs. 15.5%, p = 0.34 and 4.3% vs. 2.7%, p = 0.52).ConclusionLarge caliber venous access closure with DPSS technique was feasible, safe, and effective to achieve haemostasis after MitraClip procedure. Compared with Z-suture, use of DPSS closure was associated with a lower rate of required access related surgical intervention and postinterventional AV-fistula.